2016
DOI: 10.2138/am-2016-5599
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of manganese and sulfur in deposits on Murray Ridge, Endeavour Crater, Mars

Abstract: Mars Reconnaissance Orbiter HiRISE images and Opportunity rover observations of the ~22 km wide Noachian age Endeavour Crater on Mars show that the rim and surrounding terrains were densely fractured during the impact crater-forming event. Fractures have also propagated upward into the overlying Burns formation sandstones. Opportunity's observations show that the western crater rim segment, called Murray Ridge, is composed of impact breccias with basaltic compositions, as well as occasional fracture-filling ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 51 publications
5
67
0
Order By: Relevance
“…Our experimental results show that the scavenging pattern of trace metals associated with the formation of δ‐MnO 2 —coenrichments of Zn and Ni and depletion of Cr—is consistent with those for the Mn enrichments found by the Mars rovers (Arvidson et al, ; Lanza et al, ). This scavenging pattern is also observed for MnO 2 nodules formed in natural aqueous environments on Earth (e.g., Murray & Brewer, ), supporting the idea that deposition of MnO 2 caused the Mn enrichments within the veins at the Gale and Endeavour craters.…”
Section: Implications For Aqueous Environments and Redox States On Easupporting
confidence: 88%
See 4 more Smart Citations
“…Our experimental results show that the scavenging pattern of trace metals associated with the formation of δ‐MnO 2 —coenrichments of Zn and Ni and depletion of Cr—is consistent with those for the Mn enrichments found by the Mars rovers (Arvidson et al, ; Lanza et al, ). This scavenging pattern is also observed for MnO 2 nodules formed in natural aqueous environments on Earth (e.g., Murray & Brewer, ), supporting the idea that deposition of MnO 2 caused the Mn enrichments within the veins at the Gale and Endeavour craters.…”
Section: Implications For Aqueous Environments and Redox States On Easupporting
confidence: 88%
“…In terrestrial groundwaters in basaltic rocks, the concentrations of Mn exhibit a wide range depending on Eh (Aiuppa et al, ); for instance, low‐Eh groundwaters (e.g., –0.01 V < Eh < 0.1 V) tend to contain higher Mn abundances (e.g., >100–1,000 ppb) due to the stability of Mn 2+ under reducing conditions (Aiuppa et al, ). Thus, if the Mn enrichments found on Mars were Mn 3 O 4 , Mn (OH) 2 , and amorphous Mn (III)/Mn (II), they would have caused coenrichment of Cr as well as Zn, which is inconsistent with the observations (Arvidson et al, ; Lanza et al, ). Based on the geochemical data from terrestrial groundwater in basaltic rocks (e.g., Aiuppa et al, ), we suggest that the chemical form of the Mn oxides found by the Mars rovers is most likely MnO 2 .…”
Section: Implications For Aqueous Environments and Redox States On Eamentioning
confidence: 85%
See 3 more Smart Citations